2008
DOI: 10.1007/s00540-007-0602-2
|View full text |Cite
|
Sign up to set email alerts
|

Urinary trypsin inhibitor ameliorates renal tissue oxygenation after ischemic reperfusion in rats

Abstract: Because UTI improved renal oxygenation after reperfusion without changing cardiopulmonary parameters, the pharmacological properties of UTI, such as its renal protection and anti-shock activity, may be explained in part, by this improvement in tissue oxygenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…et al discovered that urinary trypsin inhibitor improves renal oxygenation after reperfusion without altering the cardiopulmonary parameters. [ 59 ] F.F.A. et al revealed that the infusion of physiological saline deteriorates the gas exchange caused by lung reperfusion injuries.…”
Section: Resultsmentioning
confidence: 99%
“…et al discovered that urinary trypsin inhibitor improves renal oxygenation after reperfusion without altering the cardiopulmonary parameters. [ 59 ] F.F.A. et al revealed that the infusion of physiological saline deteriorates the gas exchange caused by lung reperfusion injuries.…”
Section: Resultsmentioning
confidence: 99%